Effect of Erica sp honey against microorganisms of clinical importance: study of the factors underlying this biological activity - Feás, Xesús (2014)
This study aimed to determine the factors (phenolic compounds, flavonoids, sugars or H2O2) that contribute the most to the antimicrobial activity of heather honey samples against four yeasts and four bacteria with medical importance. To discard the effect of H2O2 in the antimicrobial activity, catalase was added. To evaluate the osmotic pressure’s effect, artificial honey was also used. Phenolic compounds and flavonoids were determined and Pearson’s correlation analysis was performed to assess whether these correlated with antimicrobial activity. The amount of phenolic compounds ranged from 630.89 ± 5.21 GAE kg−1 to 718.92 ± 4.41 GAE kg−1, while the flavonoids varied between 450.72 ± 5.67 CAE kg−1 and 673.98 ± 4.33 CAE kg−1. For the bacteria, the minimum inhibitory concentration (MIC) of the honey without catalase ranged from 1.01 ± 0.50% to 10.00 ± 4.72% and was between 2.00 ± 0.94% and 13.27 ± 5.23% for honey with catalase. Concerning the yeasts, the MICs was between 13.16 ± 4.08% and 20.00 ± 5.09% for honey without catalase and between 14.95 ± 4.16% and 25.67 ± 5.50% for honey with catalase. The elucidation of the antimicrobial factors and action mechanisms is essential for the correct use of honey in therapeutic applications.